The view from Rome : Archbishop Stagni's 1915 reports on the Ontario bilingual schools question - Stagni, Pellegrino (McGill-Queen's studies in the history of religion., 2002)
"One of the acrimonious episodes in French-English relations in Canada resulted from the bilingual schools question in Ontario in the early part of the twentieth century; the issue reinforced the divisions within the Catholic Church between francophones and anglophones. In 1916 the pope wrote a letter to the Canadian bishops in the hope of encouraging a peaceful settlement to this dispute. In his discussion the pope and his advisers relied heavily on the Apostolic Delegate of the Holy See to Canada, Archbishop Pellegrino Stagni, particularly on two reports Stagni had sent to Rome in 1915 on the problems regarding bilingual schools in the province and especially in the city of Ottawa. In The View From Rome John Zucchi translates these two reports for the first time. His introduction places the reports in context and offers historical background to the events surrounding the divisions in the church."--Jacket